2019
DOI: 10.1177/1535370219863149
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Cav1.2 channel in Timothy syndrome, from cell to bedside

Abstract: Timothy syndrome is a rare disorder caused by CACNA1C gene mutations and characterized by multi-organ system dysfunctions, including ventricular arrhythmias, syndactyly, dysmorphic facial features, intermittent hypoglycemia, immunodeficiency, developmental delay, and autism. Because of the low morbidity and high mortality at a young age, it remains a huge challenge to establish a diagnosis and treatment system to manage Timothy syndrome patients. Here, we aim to provide a detailed review of Timothy syndrome, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 104 publications
(142 reference statements)
0
17
0
2
Order By: Relevance
“…In addition to validating new variants, in vivo models will be useful for further investigation into the mechanism of TS. The various whole animal model studies were recently reviewed by Han et al (46). Careful characterization of cell and animal models of all known TS variants is essential and will aid in any future development of treatments.…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…In addition to validating new variants, in vivo models will be useful for further investigation into the mechanism of TS. The various whole animal model studies were recently reviewed by Han et al (46). Careful characterization of cell and animal models of all known TS variants is essential and will aid in any future development of treatments.…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…The most significant region contained 17 CpG sites, overlapping two genes on chromosome 22 ( CHKB and CPT1B ) with a role in pattern formation and development. Other genes with functions in regulation of developmental processes included LIMS3 , which has a role in neural tissue patterning and differentiation [ 41 ]; PRDM9 , which is involved in histone modification and hence, in regulating the epigenetic machinery [ 42 ]; and CACNA1C , which is associated with Timothy syndrome (TS), a rare neurodevelopmental disorder [ 43 ]. While methylation changes in these regions point to the possibility of the associated pathophysiology, further functional and integrative genomics analysis would be necessary to study the possible causation or correlation.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of death in TS is sudden cardiac death (SCD), likely due to fatal arrhythmias. Beta-blocker therapy has not been shown to protect against SCD ( 4 , 5 ). Dufendach et al ( 6 ), found that Nadolol conferred better protection against SCD compared to other beta blockers like propranolol.…”
Section: Discussionmentioning
confidence: 99%